Calculation of strength characteristics of the pneumatic compressor bimetallic cylinders - A. M. Bodjako; S. V. Galagajev; I. A. Melnikov; V. A. Sokolovski (Литьë и металлургия)
The stresses, occurring in a wall of the bimetallic "aluminum-cast iron" cylinder of pneumatic compressor, are estimated. The formulas for determination of the wall thickness of cylinder cast iron inserts, equivalent stresses and load factor are derived.